1997
DOI: 10.1302/0301-620x.79b5.0790816
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Prosthetic Infection Using a Cross-Linked Albumin Coating in a Rabbit Model

Abstract: We evaluated the effects of a serum protein coating on prosthetic infection in 29 adult male rabbits divided into three groups: control, albumin-coated and uncoated. We used 34 grit-blasted, commercially pure titanium implants. Eleven were coated with cross-linked albumin. All the implants were exposed to a suspension of Staphylococcus epidermidis before implantation.Our findings showed that albumin-coated implants had a much lower infection rate (27%) than the uncoated implants (62%). This may be a useful met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
1
25
0
1
Order By: Relevance
“…Some groups have found that hydrophilic materials were more resistant to bacterial adhesion than hydrophobic materials (22,23). However, An et al (24) found that hydrophobic UHMWPE disks attracted much less Staphylococcus epidermidis compared with the hydrophilic metal surface. Furthermore, there were significant increases in adhesion force of Enterococcus faecalis to NaOCl-and EDTA-treated dentin, whereas NaOCl alone did not significantly influence the adhesion force (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have found that hydrophilic materials were more resistant to bacterial adhesion than hydrophobic materials (22,23). However, An et al (24) found that hydrophobic UHMWPE disks attracted much less Staphylococcus epidermidis compared with the hydrophilic metal surface. Furthermore, there were significant increases in adhesion force of Enterococcus faecalis to NaOCl-and EDTA-treated dentin, whereas NaOCl alone did not significantly influence the adhesion force (25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of different surface treatments are being evaluated for their ability to reduce the infection rate on both orthopedic and other types of implants. (73)(74)(75)(76) If these surface treatments successfully reduce subacute infection and thereby reduce the level of adherent endotoxin without inhibiting fixation of orthopedic implants, they also might reduce aseptic loosening. An additional approach for local delivery of pharmacologic agents that target infection or inflammation is inclusion in the polymethylmethacrylate used with cemented orthopedic implants.…”
Section: Bi Et Almentioning
confidence: 99%
“…Second, it should not negatively interfere with the decisive process of osteointegration of the uncemented implants, which determines the long-term survival in arthroplasty. Regarding antimicrobial activity, there have been several studies reporting on different successful antibiotic strategies for implants in general [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Hydroxyapatite (HA) was shown to have a 1742-7061/$ -see front matter Ó 2010 Acta Materialia Inc.…”
Section: Introductionmentioning
confidence: 99%